2018
DOI: 10.1085/jgp.201711893
|View full text |Cite
|
Sign up to set email alerts
|

A model-free method for measuring dimerization free energies of CLC-ec1 in lipid bilayers

Abstract: Quantification of protein dimerization energies in lipid bilayers is hard to achieve, largely due to methodological challenges. Chadda et al. present an expansion of the single-molecule subunit-capture approach that incorporates empirical benchmarks for monomers and dimers, simplifying the process.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…These membranes are a synthetic mimic of the E. coli polar-lipid composition, containing C 16:0,18:1 tails, the most common acyl chain in biological membranes (Phillips, 2018). While CLC-ec1 forms homodimers in detergent and membranes (Maduke et al, 1999; Dutzler et al, 2002), our measurements revealed this protein complex results from association of two functionally competent monomers (Robertson et al, 2010) via a membrane-embedded hydrophobic interface (Figure 1B), with an equilibrium dimerization free energy of −10.9 kcal/mole, relative to a standard state of 1 monomer/lipid (Chadda et al, 2018). This is a remarkable finding, implying that the population of dissociated monomers in biological conditions is virtually zero.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…These membranes are a synthetic mimic of the E. coli polar-lipid composition, containing C 16:0,18:1 tails, the most common acyl chain in biological membranes (Phillips, 2018). While CLC-ec1 forms homodimers in detergent and membranes (Maduke et al, 1999; Dutzler et al, 2002), our measurements revealed this protein complex results from association of two functionally competent monomers (Robertson et al, 2010) via a membrane-embedded hydrophobic interface (Figure 1B), with an equilibrium dimerization free energy of −10.9 kcal/mole, relative to a standard state of 1 monomer/lipid (Chadda et al, 2018). This is a remarkable finding, implying that the population of dissociated monomers in biological conditions is virtually zero.…”
Section: Introductionmentioning
confidence: 75%
“…DNA constructs for CLC-ec1 C85A/H234C (WT), C85A/H234C/I201W/I422W (WW) (Chadda et al, 2016) and C85A/H234C/R230C/L249C (RCLC) were described previously (Chadda et al, 2018). Expression and purification of these CLC-ec1 variants was carried out as described earlier (Chadda et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Specifically, the measured equilibrium dimerization free energy for this complex is -10.9 kcal/mole, relative to a standard state of 1 monomer/lipid (Chadda et al, 2018). This is a remarkable finding, in that it implies that the population of dissociated monomers at biological proteinexpression levels is virtually zero.…”
Section: Introductionmentioning
confidence: 81%
“…4D,E) demonstrates no changes in the quality of images obtained in the different lipid conditions. While the cryo-EM imaging indicated no significant differences in liposome size distributions, we also examined the photobleaching probability distributions of two experimental controls: I201W/I422W, referred to as 'WW', a version of the protein with two tryptophan substitutions at the dimerization interface (Robertson et al, 2010) that reports the fixed monomer probability distribution; and R230C/L249C, or 'RCLC', a disulfide crosslinked constitutive dimer (Nguitragool and Miller, 2007) that reports the fixed dimer probability distribution (Chadda et al, 2018). Photobleaching analysis of these controls in 20% DL liposomes show dependencies on the protein mole fraction comparable to those observed for the 2:1 POPE/POPG composition (Fig.…”
Section: Short-chain Lipids Shift Clc Dimerization Equilibrium Without Effect On Protein Function or Global Membrane Changesmentioning
confidence: 99%